2022
DOI: 10.1186/s12862-022-02038-1
|View full text |Cite
|
Sign up to set email alerts
|

Seascape genomics of common dolphins (Delphinus delphis) reveals adaptive diversity linked to regional and local oceanography

Abstract: Background High levels of standing genomic variation in wide-ranging marine species may enhance prospects for their long-term persistence. Patterns of connectivity and adaptation in such species are often thought to be influenced by spatial factors, environmental heterogeneity, and oceanographic and geomorphological features. Population-level studies that analytically integrate genome-wide data with environmental information (i.e., seascape genomics) have the potential to inform the spatial dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 185 publications
0
17
0
Order By: Relevance
“…Equally interesting was the very strong explanatory power of the spring advection model for the active dispersers ’ connectivity, despite its design for larval predictions. However, this was not a novel finding: strong associations have previously been found between oceanography and dolphins’ population divergence in southern Australia, with possible relevance to hydrological adaptation and feeding specialisations (Bilgmann et al 2007, Barceló et al 2022, Pratt et al 2022). It is plausible that similar factors may be contributing to structure across current-driven habitat gradients in the present study.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Equally interesting was the very strong explanatory power of the spring advection model for the active dispersers ’ connectivity, despite its design for larval predictions. However, this was not a novel finding: strong associations have previously been found between oceanography and dolphins’ population divergence in southern Australia, with possible relevance to hydrological adaptation and feeding specialisations (Bilgmann et al 2007, Barceló et al 2022, Pratt et al 2022). It is plausible that similar factors may be contributing to structure across current-driven habitat gradients in the present study.…”
Section: Discussionmentioning
confidence: 52%
“…However, since less dispersive dolphins resident to embayment habitats are considered more likely to be impacted by extreme heatwaves (Wild et al 2019, Barceló et al 2022, the capacity for gene flow and dispersal is particularly valuable. In the present study, network analyses indicated that the strongest link between dolphin population subclusters was between Encounter (Adelaide) and Southern Spencer Gulf (Investigator Strait).…”
Section: Environmental Correlations and Potential Drivers Of Connecti...mentioning
confidence: 99%
“…In our study, geographical distance was identified as a more significant explanation of microsatellite genetic distance than sea‐surface temperature (which is unlikely to be limiting in most of the area studied) or seagrass distribution (knowledge of which is incomplete). This contrasts with indications that dugongs might make small‐scale movements in winter linked to sea temperatures at the high latitude limits to their range including Moreton Bay (Sheppard et al, 2006) and with a review of seascape‐genetic studies (Selkoe et al, 2016) that suggested that sea temperature could be as influential as geography in explaining regional‐scale population genetic structure of a number of marine mammal species (e.g., Amaral et al, 2012; Barceló et al, 2022; Fontaine et al, 2007; Pratt et al, 2022; Viricel & Rosel, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Environmental constraints to movements of marine wildlife that might affect population structuring may be difficult to identify not only because of the limited opportunities to observe their dispersal and behavior, but because there may be nonapparent barriers that impede gene flow compared to terrestrial systems (Selkoe et al, 2016). For marine wildlife, ecological barriers to movement may include geographic features, e.g., land masses, promontories, archipelagos, ice shelves, or bathymetric features (Viricel & Rosel, 2014), or less obvious physical impediments, including oceanographic features, e.g., currents and eddies (Briscoe et al, 2017), water velocity (Barceló et al, 2022), water depth, or sea surface temperature (Pratt et al, 2022; Sellas et al, 2005; Viricel & Rosel, 2014). In some cases, fine population structuring in highly mobile marine species with continuous distributions has been linked to social/cultural (e.g., Hoelzel et al, 2007; Whitehead, 2017) and/or ecological barriers, including distance between resource patches (e.g., Amaral et al, 2012; Ansmann et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…However, the role of ecological specialization on population differentiation and speciation remains poorly understood (Savolainen, Lascoux & Merila, 2013). This is particularly true for cetacean species, with only a few recent studies attempting to address the genetic basis of local adaptation (Barcelo et al, 2022;Pratt et al, 2022;de Greef et al, 2022;Louis et al, 2021;Zhou et al, 2018). Ecologically and geographical marginal environments often host populations at the edge of the species distribution and under extreme selection regimes (Johannesson & Andre, 2006).…”
Section: Local Adaptation Of Baltic Porpoises To Low Salinity Levelsmentioning
confidence: 99%